Technological Ignatian Pedagogical Content Knowledge of Language Teachers: An Enhanced Framework for Ignatian Schools - Chiu, Regiene (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study explores how the Technological Content Knowledge (TCK) framework can align with the Ignatian Pedagogical Paradigm (IPP) in Jesuit schools by employing a mixed-methods research design that combines quantitative and qualitative approaches. Data were collected through a researcher-made interview guide and the TIPACK (Technological, Ignatian Pedagogical, and Content Knowledge) survey instrument, administered to 15 senior high school (SHS) language teachers, with additional insights gathered from six focus group participants. Findings revealed that teachers demonstrate strong 21st-century higher-order thinking skills and TIPACK competencies but face challenges in fully integrating IPP, highlighting the need for mentorship and targeted training in technology use. The study’s unique contribution is the enhancement of the TPACK framework through the proposed TIPACK model, which contextualizes technology integration within Jesuit education by explicitly aligning it with the Ignatian Pedagogical Paradigm. This contribution is both theoretical and practical, offering a framework that connects faith-based educational values with 21st-century teaching competencies while informing teacher training, curriculum development, and online education standards in Ignatian schools.